1999
DOI: 10.1111/j.1540-8167.1999.tb00195.x
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐Gated Na+ Channel Activity and Connexin Expression in C×43‐Deficient Cardiac Myocytes

Abstract: Despite a genetic inability to produce Cx43 and a developmental history that culminates in marked gross cardiac morphologic abnormalities, premature death, and myocardial inexcitability ex vivo, cardiac Na+ channel distribution and function appear to be normal in Cx43 null hearts. Although intimate structural and functional interrelationships have been described between ion channels and gap junction channels, expression and function of Na+ channels is not affected by the absence of Cx43.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
2
27
0
1
Order By: Relevance
“…The observation that the dV/dt max is not reduced in the Cx43 Ϫ/Ϫ embryos suggests that the slow propagation seen at this time point is not a result of a concurrent reduction in excitatory currents. This is consistent with the findings of Johnson et al, 40 who studied sodium currents in Cx43 Ϫ/Ϫ animals at term. However, that study found no increase in the upstroke velocity in isolated myocytes.…”
Section: Microelectrode Recordings In 155-dpc Heartssupporting
confidence: 93%
See 1 more Smart Citation
“…The observation that the dV/dt max is not reduced in the Cx43 Ϫ/Ϫ embryos suggests that the slow propagation seen at this time point is not a result of a concurrent reduction in excitatory currents. This is consistent with the findings of Johnson et al, 40 who studied sodium currents in Cx43 Ϫ/Ϫ animals at term. However, that study found no increase in the upstroke velocity in isolated myocytes.…”
Section: Microelectrode Recordings In 155-dpc Heartssupporting
confidence: 93%
“…However, that study found no increase in the upstroke velocity in isolated myocytes. 40 The paradoxic increase in the upstroke velocity gives credence to a computational prediction of Rudy and Quan 41 that in the presence of unchanged excitatory currents, the higher input resistance of poorly coupled cells must result in higher upstroke velocities. Note that only RV and not LV conduction velocity was found to be reduced in the Cx43 Ϫ/Ϫ heart at 15.5 dpc.…”
Section: Microelectrode Recordings In 155-dpc Heartsmentioning
confidence: 77%
“…Aliquots containing 7 g of total protein were analyzed by SDS polyacrylamide gel electrophoresis, and Cx43 signal was quantified as described in detail in previous studies. 6 In all experiments, Cx43 signal in experimental preparations was compared with signal from control cultures (cells incubated in serum-free medium for 1 hour but not subjected to stretch or exposed to VEGF or antibodies), which was normalized to a value of 1.0.…”
Section: Immunoblot Assay Of Cx43 Expressionmentioning
confidence: 99%
“…Connexin 37 (Cx37), Cx40, Cx43, Cx45, Cx46, and Cx50 are expressed in mammalian cardiomyocytes (Darrow et al 1995;Saffitz et al 2000;Polontchouk et al 2002). Studies using Cx43-deficient mice have demonstrated that Cx43 is the principal protein for ventricular electrical coupling (Reaume et al 1995;Ya et al 1998;Johnson et al 1999;Gutstein et al 2001).…”
mentioning
confidence: 99%